School feeding in Ethiopia: a scoping review - Samson Mideksa; Tsegaye Getachew; Firmaye Bogale; Ermias Woldie; Desalegn Ararso; Aregash Samuel; Meron Girma; Masresha Tessema; Mamuye Hadis (BMC, 2024)
Abstract Introduction Undernutrition is a major public health problem in developing countries, especially in Sub-Saharan Africa. Undernourished children are smaller and have low weight. To solve this issue, school feeding (corn-soya blend, vegetable oil) started in 1994 in Ethiopia. Thus, this scoping review aims to map the evidence relating to school feeding programs and their potential role in managing children`s nutrition in Ethiopia. Methods This scoping review is informed by the methodological framework of Arksey & O'Malley for scoping reviews and recommendations on the framework by Levac and colleagues. The databases searched included the Education Resources Information Centre, International Initiative for Impact Evaluation, Cochrane Library, MEDLINE, and Google Scholar. To ensure its comprehensive search, grey literature sources were searched. The search was undertaken on 26 April 2023. Studies on school feeding, such as coverage, and studies that evaluate the educational and nutritional impacts of school feeding in Ethiopia, regardless of study designs, were included. Reports (publications) about school feeding without scientific methodology were excluded. Result Twenty-seven studies were included in this review. It includes cross-sectional, prospective cohort, laboratory-based analysis, experimental, case study, and qualitative study designs. The school feeding program results were inconclusive, while some indicate a positive effect on body mass index, height, thinness, anemia, weight, dropout rate, class attendance, and enrollment. The others showed that the school feeding program did not affect stunting, thinness, weight, hemoglobin level, enrollment, attendance, dropout rate, and academic achievement. Factors affecting school feeding programs negatively include poor quality food and financial constraints. However, no literature on school feeding program coverage was found. Conclusion School feeding programs improved nutritional status, and academic performance, although some studies show any effect. Poor-quality food provisions and financial constraints affect school feeding programs. There are mixed findings, and further research is required to determine the effect of school feeding programs conclusively. To ensure the program's sustainability, it should be supported by a national policy, and budget allocation is needed. In addition, more evidence should be generated to show the coverage of school feeding programs in Ethiopia.